Controlling the Interparticular Distances of Extended Non-Close-Packed Colloidal Monolayers - Schmudde, Madlen (Langmuir : the ACS journal of surfaces and colloids, 2020)
A versatile method for the preparation extended, well-ordered, non-close-packed monolayers of silica nanoparticles (137 ± 4 nm diameter) with adjustable interparticle distances is presented, which is based on a simple self-assembly procedure using aqueous dispersion with different ionic strengths. It is shown that these structures can be successfully transferred to air without suffering from aggregation. Scanning electron microscopy (SEM) is used to characterize the structures after transfer into the atmosphere. These investigations were combined with a quartz crystal microbalance with dissipation (QCM-D) experiments to follow the self-assembly process in solution. The nearest-neighbor distance distribution reveals a monotonous decrease of the average nearest-neighbor distance from 290 to 200 nm with increasing ionic strength from 0.05 to 1 mM, which indicates an increased shielding of the electrostatic interaction with increasing ionic strength. The observed saturation coverages for all studied ionic strengths are well explained with an effective hard-sphere model in which the saturation coverage is limited by Coulomb repulsion. However, at ionic strengths above 1 mM, significant amounts of aggregates are found in the dried samples, suggesting that the observed aggregates at high ionic strengths are formed during the drying process caused by capillary forces between the particles. Tuning the barrier for lateral diffusion, e.g., by changing the surface morphology or functionalization of the particles will offer a route to further extend the range of particle distances. The present approach can be easily expanded to a broad range of colloidal materials on surfaces, while it only requires low-cost laboratory equipment